2010
DOI: 10.1364/oe.18.018278
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency fiber-to-chip grating couplers realized using an advanced CMOS-compatible Silicon-On-Insulator platform

Abstract: A new generation of Silicon-on-Insulator fiber-to-chip grating couplers which use a silicon overlay to enhance the directionality and thereby the coupling efficiency is presented. Devices are realized on a 200 mm wafer in a CMOS pilot line. The fabricated fiber couplers show a coupling efficiency of −1.6 dB and a 3 dB bandwidth of 80 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
198
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(203 citation statements)
references
References 12 publications
4
198
0
1
Order By: Relevance
“…According to [7], [8], an extra Si overlay (polycrystalline or amorphous) with a thickness of 160 nm can be locally deposited on top of a 1D GC to increase the fraction of the upward diffracted power, so as to increase the waveguide-tofiber coupling efficiency. The cross section of such a GC is shown in figure 2(a).…”
Section: (B)) L(α)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to [7], [8], an extra Si overlay (polycrystalline or amorphous) with a thickness of 160 nm can be locally deposited on top of a 1D GC to increase the fraction of the upward diffracted power, so as to increase the waveguide-tofiber coupling efficiency. The cross section of such a GC is shown in figure 2(a).…”
Section: (B)) L(α)mentioning
confidence: 99%
“…On the other hand, studies on improving the coupling efficiency and bandwidth of a GC have also been intensively reported [2], [6]. We reported that a silicon overlay can be deposited on top of a 1D GC to increase the coupling efficiency [7], [8]. However, there has been little work so far on the designs that combine high coupling efficiency with low back reflection in a CMOS-compatible SOI platform.…”
Section: Introductionmentioning
confidence: 99%
“…This method has already been well studied at telecom wavelengths [42,43], with coupling losses as low as -0.75 dB experimentally attained by Luxtera [44]. Additionally, grating couplers can be placed anywhere on the chip, affording flexibility in input/output coupling location.…”
Section: Grating-coupled Ring Resonators In a Sos Platformmentioning
confidence: 99%
“…We extended the framework to control our measurement hardware, and we can incorporate test and measurement information in our design. For instance, we can extract the positions of the optical input and output ports (using vertical grating couplers [11]) from the mask layout to program a probe station equipped with high-precision fiber position stages.…”
Section: Integrated Simulationmentioning
confidence: 99%